Effectiveness of Motor Skills Development in 5th-7th Grade Girls at Different Modes of Physical Exercises - Olga Ivashchenko; Tamila Abdulkhalikova; Miroslava Cieślicka (Physical Education Theory and Methodology, 2017)
The objective is to determine the influence of the physical exercises modes on effectiveness of motor skills development in 5th-7th grade girls.